631 Development of highly efficacious and safe targeted cancer immunotherapy via IL12-based TMEkine™ platform. (9th November 2020) - Lee, Dahea; Kim, Donggeon; Ryu, Soomin; Lee, Byoung Chul
Abstract : Background: We developed tumor microenvironment-targeting immunocytokine or TMEkine™ utilizing strong anti-tumoral effect of interleukin 12 (IL-12). In this effort, we created a bi-specific 1+1 antibody fusion with conventional knob-in-hole technology where anti-CD20 was paired with IL-12 fc fusion arm. A couple of IL-12 muteins were used in our therapeutic molecules to reduce systemic toxicity. IL-12 has been known for a key orchestrator in immune response. The main actions of IL-12 include the induction of CD4+ Th0 cells toward Th1 type and enhancement of IFN-γ production, stimulation of cytotoxicity and growth of natural killer (NK) cells and CD8+ T cells. For these reasons, IL-12 has long been considered as a potential therapeutic molecule for treating cancers by enhancing immune activity toward tumor cells. However, systemic administration of IL-12 showed poor efficacy and severe adverse effects. With our therapeutic approach of tumor targeting and attenuated IL-12 mutein, we expect that our IL12-based TMEkine™ holds great promise for the future of cancer immunotherapy.In this study, we targeted CD-20 expressing cancers such as B-cell lymphoma with our anti-CD20/IL-12 mutein TMEkine. We evaluated the biological activity of our molecules with in vitro and in vivo efficacy and safety. Methods: The target specific binding to CD20 and IL-12 receptor was analyzed by FACS and ELISA. Biological activities as signaling transduction and T cell activation were confirmed in vitro using HEKblue IL12 cell line, primary human T cells and NK cells. The anti-tumor efficacy of TMEkine (CD20-IL-12) was assessed in A20 lymphoma syngeneic mouse model. To demonstrate long term protection to A20, the cured five mice after TMEkine administration were re-challenged with A20 and 4T1 cells. Results: First, we analyzed the specific binding of our TMEkine molecules to CD20 expressing B-cell lymphoma cell lines (such as Raji). We showed that TMEkine (CD20-IL-12) binds to Raji and Ramos, which express CD20, but not to Jurkat, which does not express CD20. We also showed that TMEkine molecules bind to IL-12 receptor in a dose-dependent manner. pSTAT4 alphaLISA assay revealed that TMEkine (CD20-IL-12) transduces STAT4 signaling. In our IL-12 mutein, key residues for heparin binding were mutated. The biological activity of our mutein molecule was attenuated due to this change in human PBMC. In addition, our TMEkine molecules significantly induced IFN-γ secretion from primary human T cells and NK cells. An A20 B-cell lymphoma syngeneic mouse model was utilized to investigate the anti-tumor activity of TMEkine (CD20-IL-12). TMEkine molecules were injected three times with Q3D intraperitoneally. Tumor growth was substantially reduced and no cytotoxicity was observed. To further investigate the underlying mechanism, we analyzed tumor infiltrating lymphocytes (TIL) and as expected, we observed the increase in the number of CD8+ T cells in TIL, compared to control group. Interestingly, our tumor re-challenge result demonstrates that TMEkine (CD20-IL-12) protected animals from tumor recurrence implying that immunologic memory response was generated upon our TMEkine (CD20-IL-12) treatment. Conclusions: Altogether, our data suggest that TMEkine (CD20-IL-12) as an efficacious tumor targeting cytokine opening up a new avenue for the treatment of B-cell lymphoma.